2020
DOI: 10.1021/acs.joc.0c01312
|View full text |Cite
|
Sign up to set email alerts
|

Bungsteroid A: One Unusual C34 Pentacyclic Steroid Analogue from Zanthoxylum bungeanum Maxim

Abstract: Bungsteroid A (1), possessing an unreported carbon skeleton, was isolated from the pericarps of Zanthoxylum bungeanum Maxim. It represents the first carbon skeleton of a C34 steroid analogue featuring a unique 6/6/6/6/5-fused pentacyclic skeleton, which has been determined by spectroscopic methods, quantum-chemical 13C NMR, ECD calculations, and calculations of optical rotations. Bungsteroid A showed the antiproliferative effects against HepG2, MCF-7, and HeLa cell lines with the IC50 values of 56.3 ± 1.1, 64.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…The absolute configuration of 1 was confirmed by the quantum-mechanical time-dependent density functional theory (TDDFT) calculations. , The theoretically calculated ECD spectrum of 1 showed a negative Cotton effect at 214 (Δε −5.17), which was consistent with the experimental CD spectrum at 220 (Δε −7.73) (Figure ). Moreover, colorless columnar crystals were yielded in a dichloromethane (CH 2 Cl 2 ) solution at room temperature.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…The absolute configuration of 1 was confirmed by the quantum-mechanical time-dependent density functional theory (TDDFT) calculations. , The theoretically calculated ECD spectrum of 1 showed a negative Cotton effect at 214 (Δε −5.17), which was consistent with the experimental CD spectrum at 220 (Δε −7.73) (Figure ). Moreover, colorless columnar crystals were yielded in a dichloromethane (CH 2 Cl 2 ) solution at room temperature.…”
Section: Resultssupporting
confidence: 73%
“…Compound 1 was screened for antiproliferative effects against BEL-7402, HepG2, and Huh-7 hepatocellular carcinoma cell lines and HeLa cervical cancer cell lines, which exhibited the inhibition with the IC 50 values of 5.67 ± 1.43, 21.84 ± 1.62, 25.5 ± 3.14, and 15.46 ± 0.69 μM, respectively. The effect of 1 in different concentrations on morphology of BEL-7402 cell lines under microscope showed that 1 induced cell death in a dose-dependent manner (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9] A variety of steroids are widely used as anticancer, anti-inflammatory, immunosuppressive, progestational, diuretic, anabolic and contraceptive agents as well as in other applications. [10][11][12][13][14][15][16][17] Certain structural modifications of the rigid tetracyclic steroidal skeleton induced changes of biological response, providing compounds with pronounced biological activity. Pentacyclic steroids are among them and belong to an important class of natural products, which, depending on the fifth cycle condensation position, can both maintain hormonal properties and completely suppress them.…”
Section: Introductionmentioning
confidence: 99%
“…Pentacyclic steroids are among them and belong to an important class of natural products, which, depending on the fifth cycle condensation position, can both maintain hormonal properties and completely suppress them. [17][18][19][20][21][22][23] There are many examples of pentacyclic steroidal derivatives of pharmacological and biological importance. [24][25][26][27][28] However despite the diversity of biological activity exhibited by pentacyclic steroids, their syntheses are often hard and multistep.…”
Section: Introductionmentioning
confidence: 99%